2018
DOI: 10.1016/j.jaridenv.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Dryness affects burrowing depth in a semi-fossorial amphibian

Abstract: The fossorial life-history emerged as a response to hostile environmental conditions, such as extreme temperatures and dryness. It evolved independently in different lineages of amphibians, which are particularly vulnerable to dehydration and require a continuous level of humidity because of their permeable skin. For the first time, we test the hypothesis that amphibians are able to adapt their fossorial behaviour to substrate humidity, using the Pacific horned frogs (Ceratophrys stolzmanni) from the Ecuadoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…However, we found that the differences in relative size of hindlimbs did not affect jumping ability in the case of horned frogs; the main factor determining locomotor performance was the body size of juveniles. In fossorial frogs, the leg length in relation to the body size is probably less flexible compared to non-fossorial species of frogs [24,53], as a result of managing the contrasting selective pressures of avoiding predation or desiccation and efficient burrowing [54]. Alternatively, the variation of leg length might have been too small to determine a measurable difference in jumping distance [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found that the differences in relative size of hindlimbs did not affect jumping ability in the case of horned frogs; the main factor determining locomotor performance was the body size of juveniles. In fossorial frogs, the leg length in relation to the body size is probably less flexible compared to non-fossorial species of frogs [24,53], as a result of managing the contrasting selective pressures of avoiding predation or desiccation and efficient burrowing [54]. Alternatively, the variation of leg length might have been too small to determine a measurable difference in jumping distance [55].…”
Section: Discussionmentioning
confidence: 99%
“…obs.). The froglets were kept individually, in mesh-covered (to prevent escape) plastic tanks (21 × 15 cm, 12 cm high), with a 5-cm layer of moist soil that allowed natural burrowing behaviour [54]. Temperature, relative humidity and light regime were similar to the ones in natural habitat, except for a roof that provided protection from direct sun heating.…”
Section: Animal Carementioning
confidence: 99%
“…However, we found that the differences in relative size of hindlimbs did not affect jumping ability in the case of horned frogs; the main factor determining locomotor performance was the body size of juveniles. In fossorial frogs, the leg length in relation to the body size is probably less flexible compared to non-fossorial species of frogs [24,53], as a result of managing the contrasting selective pressures of avoiding predation or desiccation and efficient burrowing [54]. Alternatively, the variation of leg length might have been too small to determine a measurable difference in jumping distance [55].…”
Section: Discussionmentioning
confidence: 99%
“…Jumping performance tests were taken on the 23 April 2015, when individuals had reached developmental stage G46. During the two days prior to these trials, the juveniles did not receive any food, so that the presence of food in the digestive system would not influence the results [53]. The lack of feeding during metamorphosis is normal in anurans due to changes in their digestive system [64].…”
Section: Methodsmentioning
confidence: 99%
“…Jumping performance tests were done on the 23rd of Apr 2015, when individuals had reached developmental stage G46. During the two days prior to these trials, the juveniles did not receive any food, so that the presence of food in the digestive system would not influence the results [53]. The lack of feeding during metamorphosis is normal in anurans due to changes in their digestive system [64].…”
Section: Methodsmentioning
confidence: 99%